Adherence to treatment guidelines and survival for older patients with stage II or III colon cancer in Texas from 2001 through 2011. Issue 4 (15th November 2017) - Zhao, Hui; Zhang, Ning; Ho, Vivian; Ding, Minming; He, Weiguo; Niu, Jiangong; Yang, Ming; Du, Xianglin L.; Zorzi, Daria; Chavez‐MacGregor, Mariana; Giordano, Sharon H.
Abstract : BACKGROUND: Treatment guidelines for colon cancer recommend colectomy with lymphadenectomy of at least 12 lymph nodes for patients with stage I to stage III disease as surgery adherence (SA) and adjuvant chemotherapy for individuals with stage III disease. Herein, the authors evaluated adherence to these guidelines among older patients in Texas with colon cancer and the associated survival outcomes. METHODS: Using Texas Cancer Registry data linked with Medicare data, the authors included patients with AJCC stage II and III colon cancer who were aged ≥66 years and diagnosed between 2001 and 2011. SA and adjuvant chemotherapy adherence rates to treatment guidelines were estimated. The chi‐square test, general linear regression, survival probability, and Cox regression were used to identify factors associated with adherence and survival. RESULTS: The rate of SA increased from 47.2% to 84% among 6029 patients with stage II or stage III disease from 2001 to 2011, and the rate of adjuvant chemotherapy increased from 48.9% to 53.1% for patients with stage III disease during the same time period. SA was associated with marital status, tumor size, surgeon specialty, and year of diagnosis. Patient age, sex, marital status, Medicare state buy‐in status, comorbidity status, and year of diagnosis were found to be associated with adjuvant chemotherapy. The 5‐year survival probability for patients receiving guideline‐concordant treatment was the highest at 87% for patients with stage II disease and was 73% for those with stage III disease. After adjusting for demographic and tumor characteristics, improved cancer cause‐specific survival was associated with the receipt of stage‐specific, guideline‐concordant treatment for patients with stage II or stage III disease. CONCLUSIONS: The adherence to guideline‐concordant treatment among older patients with colon cancer residing in Texas improved over time, and was associated with better survival outcomes. Future studies should be focused on identifying interventions to improve guideline‐concordant treatment adherence. Cancer 2018;124:679‐87. © 2017 American Cancer Society . Abstract : Older patients with colon cancer appear to have a lower adherence rate to guideline‐recommended treatments. The results of the current study reveal several modifiable factors that may improve the survival of patients with colon cancer.